Communication Strategies Used by Indonesian Teacher toward Thai Students in Teaching English at Chariyhatam Suksa Foundation School - Sarwo Edy (ELITE Association Indonesia, 2023)
This research aimed to find out Communication Strategies used by Indonesian teacher in teaching English and how Indonesian Teacher implement those Communication Strategies toward Thai Students at Chariyhatam Suksa Foundation school in Thailand. This research is a qualitative method that is described in a descriptive manner. The focus of this study was an Indonesian teacher who teaches English at Chariyhatam Suksa Foundation School. To collect the data the researcher used Document Analysis and interviews. In analysis data, first researcher manages the data that be collected. After that, the researcher reads the result of the data. Then, classified based on the kinds of communication strategies and how the teacher implements these strategies in the class. Furthermore, the researcher describes all the data that has been obtained. The last, the researcher interprets the data and explain deeply about communication strategies and these implementation. The findings exposed that in teaching English toward Thai Students the teacher used three kinds of communication strategies they are Code switching, Nonlinguistic Strategy and filler or Hesitation. In addition the teacher also used other strategies that were not suggested in the theory it is Repetition strategies. Forward, the teacher also implement these communication strategies in the class and the implementation has good enough for the students Keywords: Teaching English, Communication Strategy, Chariyhatam Suksa Foundation School